(untitled) (Revista Cientifica Ingenio Magno, 2020)
The study presents the behavior of the ICACOSU Index along the Los Pozos – Aquitaine microbasin and the influence of temporal variations on the water quality of the same, relating them to the anthropic activities present in it. When assessing the water quality in the Los Pozos- Aquitaine microbasin, identifying the influence of anthropogenic factors on the system for this reason the type of descriptive research was used, which allows to know the water quality of the microbasin in three representative points: birth, hydrographic station the Criadero and mouth to Lake Tota; taking into account the variability of precipitation, two tracer tests are also carried out in two sections of the current to determine the dispersion coefficient and travel time of the plotter, as additional information to the study.